2022
DOI: 10.1021/acsomega.1c03018
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology with Experimental Investigation of the Mechanisms of Rhizoma Polygonati against Prostate Cancer with Additional Herbzymatic Activity

Abstract: A combination therapy of RhizomaPolygonati (RP) with goji (Lycium chinense) has earned a long history in the prescriptions to promote male health. However, the mechanisms at both molecular and nanoscale quantum levels are unclear. Here, we found that processed RP extract induces apoptosis and cell cycle arrest in cancer cells, thereby inhibiting prostate cancer cell proliferation enhanced by processed goji extract associated with an augment of the nanoscale herbzyme of phosphatase. For network pharmacology ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Recently, it was reported that a herbzyme extracted from the RP of Mount Tai can enhance phosphatase activity as a co-enzyme and anti-cancer agent [144][145][146] . The herbzyme activity can be enhanced by CaCl 2 (0.25M), whereas control protein-based phosphatase ALP decreased enzyme activity at 0.75M by the metal calcium solution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that a herbzyme extracted from the RP of Mount Tai can enhance phosphatase activity as a co-enzyme and anti-cancer agent [144][145][146] . The herbzyme activity can be enhanced by CaCl 2 (0.25M), whereas control protein-based phosphatase ALP decreased enzyme activity at 0.75M by the metal calcium solution.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effect developed by nanozymes with oxidizing characteristics can be attributed to the reactive oxygen species (ROS) [50]. Different elements, natural products or metal-doped carbon-based nanozymes are developed to be used as sensor, anti-cancer therapeutic reagents [52][53][54][55][56]. However, whether this nanozyme induced cell death is reversible is largely unknown, not to mention their roles in drug resistance and DNA repair crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have recently employed this advanced technique to identify targets and pathways for phytoconstituents found in a variety of plants. [38,39] Therefore, network pharmacology has been performed to highlight the interactions between compounds, genes and signaling pathways in detail. Before the construction of the network, KEGG pathways were downloaded from the STRING 11.5 analysis section, and the signaling pathways which are involved in epilepsy were selected (Table S7).…”
Section: Network Pharmacology Analysismentioning
confidence: 99%